Modified AODV Techniques for Detection and Prevention of Gray Hole Attack in MANET (International Journal of Engineering and Computer Science, 2017)
Compared the On-Demand (DSR and AODV) and Table-Driven (DSDV) routing protocols by changing the nodes number and evaluated the metrics “end-end delay, packet delivery ratio, packets dropped, throughput”. In case of packet delivery ratio, AODV performs better than DSDV when number of nodes are high, but DSDV performs better than two protocols in as far as throughput is concerned. So, in real time traffic scenario AODV is favoured as compared to DSR and DSDV. Further, the attacker selects only those genuine nodes through more than a threshold number of alternative paths pass through, thereby facilitating the attacker to use less number of nodes. So the attack scheme is power aware. Finally we also propose IDS to detect the proposed energy aware Gray hole attack. NS2 experimental results show the validity of the proposed attack